Software products for high-frequency simulation of fractal antennas - Imanbayeva А.К.; Temirbayev А.А.; Karibayev B.А.; Syzdykova, R.N.; Tolegenova А.; Kossov, D.N. (Recent Contributions to Physics, 2017)
The design of microwave electronic equipment has its own specifics, which is mainly determined by its ability to receive high radio technical characteristics. In the market, there are many software products for simulation of microwave devices. They offer a variety of approaches for computer solution of electrodynamics problems. Modern computer-aided design (CAD) systems of UHF allow developing at various stages of the device concept design and, to the simulation of system behavior, using a wide range of modeling tools. This article provides an overview of the electrodynamics analysis software and design of microwave devices, including fractal antennas. Ansoft Corporation company system High Frequency System Simulator (HFSS) of is the most optimal system for our task. HFSS is the most advanced in the industry of RF & microwave and high-speed digital electronic devices. We conducted an analysis on the use of these programs by various researchers. Also presents its own results of computer simulation of fractal antennas of three different types.